Prognostic value of the MDACC–NLR score in extensive-stage small-cell lung cancer treated with first-line chemoimmunotherapy - Li, Dan; Li, Xiaolin; Liu, Ning; Wang, Bo; Jin, Hui; Liu, Yan; Liu, Jiayin; Zhang, Xue; Wang, Long; Fan, Zhisong; Feng, Li; Han, Jing; et al. (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the prognostic performance of six scoring systems in predicting outcomes of first-line chemo-immunotherapy in patients with extensive-stage small cell lung cancer (ES-SCLC), aiming to guide individualized treatment.MethodsThis single-center retrospective study included 197 ES-SCLC patients treated with first-line chemo-immunotherapy. Clinical and laboratory data were collected, including baseline characteristics, treatment responses, and survival outcomes. The prognostic impact of six scoring systems (RHM, MDACC, MDACC+NLR, MDA-ICI, LIPI, GRIm) was assessed using univariate and multivariate Cox regression analyses for progression-free survival (PFS) and overall survival (OS). Kaplan–Meier analysis was conducted for risk stratification.ResultsBy the last follow-up (October 15, 2024), the median follow-up was 12 months, with 113 deaths (57.3%). The objective response rate was 75.6%. ECOG ≥1, lung metastasis, and liver metastasis were independent predictors of poorer PFS and OS. Among the scoring systems, only MDACC+NLR effectively stratified patients: low-risk patients had significantly longer PFS and OS (both p = 0.02). MDACC alone did not distinguish PFS among risk groups (p = 0.17) but showed significant OS differences (p = 0.02). Other systems (RHM, MDA-ICI, LIPI, GRIm) lacked significant discriminatory ability for both PFS and OS (all p > 0.05).ConclusionECOG ≥1, lung metastasis, and liver metastasis are adverse prognostic factors for ES-SCLC patients receiving first-line chemo-immunotherapy. The MDACC+NLR scoring system provides superior predictive value for treatment outcomes and survival, supporting its potential utility for clinical risk stratification.